Peran Alternatif Penyelesaian Sengketa Dalam Menyelesaikan Konflik Bisnis Di Indonesia - Putri .; Siti Inayah; Muhammad Reihan; Holijah . (GLOBAL SCIENTS PUBLISHER, 2026)
Alternative Dispute Resolution (ADR) has become an increasingly relevant mechanism in resolving civil disputes outside the formal court system in Indonesia, particularly due to the inefficiency of litigation processes which are often time-consuming, costly, and procedurally rigid. This study aims to analyze the effectiveness of ADR in resolving civil disputes and to identify its advantages and challenges compared to litigation. The research employs a normative juridical approach with descriptive-analytical methods, utilizing statutory and conceptual approaches supported by literature review, including international references. The findings reveal that ADR offers significant advantages in terms of efficiency, cost reduction, and procedural flexibility. Mediation is the most widely used method due to its ability to produce mutually beneficial agreements, while arbitration ensures legal certainty through final and binding decisions, and negotiation allows flexible settlements. A case illustration involving a contractual dispute further confirms the effectiveness of ADR in practice. However, challenges remain, particularly limited public awareness and lack of professional expertise. Therefore, strengthening institutional support and legal literacy is necessary to optimize ADR implementation.